2012
DOI: 10.7727/wimj.2012.026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High-risk Sexual Behaviour in Jamaican Adults and Its Relationship to Sociodemographic and Religious Factors: Findings from the Jamaica Health and Lifestyle Survey 2007−2008

Abstract: Objective: To estimate the prevalence of high-risk sexual behaviours among Jamaican adults and evaluate associations with sociodemographic and religious factors. Methods: We performed a cross-sectional study, using a nationally representative sample of Jamaicans, 15−74 years old. Participants completed an interviewer-administered questionnaire including questions on sexual activity, sociodemographic factors and religious practice. Having two or more sexual partners in the past year, non-use of condoms among pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…It is considered that these results are similar among seniors from different countries, as international papers also showed some of the factors, such as the study of Jamaican where 31% of men and 5% of women aged between 55 and 74 years old, engage in high-risk sexual practices [19].…”
Section: Vulnerability Of Elderly To Hiv/aidsmentioning
confidence: 71%
See 1 more Smart Citation
“…It is considered that these results are similar among seniors from different countries, as international papers also showed some of the factors, such as the study of Jamaican where 31% of men and 5% of women aged between 55 and 74 years old, engage in high-risk sexual practices [19].…”
Section: Vulnerability Of Elderly To Hiv/aidsmentioning
confidence: 71%
“…Elderly people who reported practice their religion and respect the established dogmas had less sexual risk behavior in a study conducted in Jamaica [19].…”
Section: Religious Beliefs Of Elderly About Hiv/aidsmentioning
confidence: 99%
“…It is interesting to note that the Jamaica Health and Lifestyle Study II (JHLS II) which is a survey of a nationally representative sample in Jamaica, reported a STI prevalence in men of 18.2% (95% CI, 15.4%–21.3%) 36 . The prevalence of a history of STIs in our study was significantly higher than what has been reported in Jamaica and may reflect a bias due to recruitment of the study sample from the hospital and urologist practices.…”
Section: Discussionmentioning
confidence: 99%
“…This includes those with a history of ≥1 STI. [15][16][17] Currently, PFSHS triage these young people to their GPs for sexual healthcare.…”
Section: Discussionmentioning
confidence: 99%